Carboxymethyl mungbean starch as a new pharmaceutical gelling agent for topical preparation - Ornanong S. Kittipongpatana (2018)
An application of carboxymethyl mungbean starch (CMMS) as a gelling agent in the topical pharmaceutical preparation was investigated. CMMS was prepared using specific conditions that yielded a high-viscosity product. Polymer gels and gel bases were prepared at 1-10% (wt/wt), and physicochemical studies were carried out in comparison with four standard gelling agents: carbopol 940 (CP), hydroxypropylmethyl cellulose (HPMC), methyl cellulose (MC), and sodium carboxymethyl cellulose (SCMC). Piroxicam was used as a model drug to study the drug release profile of the gel formulations. The tackless, greaseless, and transparent CMMS gels exhibited pseudoplastic behavior with thixotropy at concentrations less than 5% (wt/wt). At a concentration of 5% (wt/wt) and higher, the semisolid gels showed plastic flow characteristics. Viscosity and X-ray diffraction results indicated a good compatibility between CMMS and the acidic piroxicam. No precipitation of piroxicam or phase separation was observed during a stability test. The release rate of piroxicam from 3% (wt/wt) CMMS gel was 1,003.79 ± 105.08 μg/cm2, which was comparable with 947.66 ± 133.70 μg/cm2 obtained from a 0.5% (wt/wt) carbopol formulation. The release profiles of both formulations were consistent and remained unchanged after 2 months' storage. Viscosity played an important role in controlling the release rate of low concentration CMMS formulations by regulating the drug diffusion. At a concentration of 5% (wt/wt) CMMS and higher, the release rates of piroxicam were not significantly different. A plausible explanation based on the nature of the gelling agent was proposed. Stability and drug release profiles of CMMS and commercial gelling agents were compared. The results supported the potential use of CMMS as a new, effective gelling agent for topical gel preparation. Copyright © Informa UK, Ltd.